Economic Potential of Kazakhstan’s Regions: Methodology, Comparative Analysis and Rating Assessment - Zh. Zh. Yeszhanova; M. A. Kalikov; T. Y. Abdykadyr (Экономика: стратегия и практика)
The purpose of this study is to develop and test a methodology for comparative assessment of the economic potential of regions in the example of the regions of Kazakhstan. Based on the review of various approaches to the concept and structure of the economic potential (EP) of the region, the author’s approach to the definition, content and methodology of assessment is proposed in the article. The authors have processed statistical material for all regions of Kazakhstan for the period from 2000 to 2021 (according to some indicators, the analyzed periods vary). As a method of EP analysis, the authors propose to use a multidimensional comparative analysis, which allows for obtaining a comprehensive rating assessment of the region by the level of economic potential. The authors analyzed the economic potential of all regions of Kazakhstan on the basis of selected criteria of socio-economic indicators averaged over the studied period of time. The authors examined in detail the positions of the country’s regions on each component: investment, innovation, labor, industrial, social, and environmental potentials, as well as on the whole on the complex indicator of economic potential. According to the results of the rating assessment, Atyrau region, Almaty, and Astana, received the highest levels of economic potential, Mangistau and Almaty regions received low scores. The comparative analysis made it possible to identify the strengths and weaknesses of the regions of Kazakhstan to determine in which directions to develop and improve positions. The approach developed in the article to the comparative analysis of the economic potential of regions will allow classifying regions both by individual components of the EP and in general, to obtain a comprehensive assessment of the level of the EP.